Evaluating the impact on the Barbados agricultural sector of altering the protective policy regime : special reference to the Common External Tariff - Antoine, Patrick A. (IICA BridgetownBB, 1994)
Uses a LASPEYRES quantity index of agricultural production to assess trends in agricultural production between 1980 and 1991. Identifies and discusses government policies which impact upon the agricultural sector and explains the contribution of CARICOM policies such as the Common External Tariff. Identifies the structure of domestic tariff and non-tariff barriers as well as other forms of protection. Discusses the role of various other support schemes which impact upon the agriculture sector.